Unveiling Extra-Institutional Agency in Nationalist Contention: Transformative Events and Grassroots Mobilizations in Scotland and Catalonia (1980s-2000s) - Carla Mannino (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The literature on nationalist movements in Western democracies has almost exclusively focused on ethno-nationalist parties by attributing to them the key-role of “ethnic entrepreneurs”. Yet, non-institutional actors such as social movement organizations and grassroots groups can significantly impact the history of territorial contention and reshape movements. Their role is thus explored in the Scottish and Catalan struggles for selfdetermination between the 1980s and the 2000s. Firstly, the historical analysis of transformative events shows how the latter were set in motion by non-institutional actors. While Scottish organizations and groups operated to foster cross-party cooperation, the Catalan counterparts operated to mobilize society and popular support. Secondly, a thematic analysis of primary sources shows that the mobilizations fuelled by these events produced organizational and cultural changes in both nationalist movements. These changes left their legacy suggesting that former grassroots mobilizations made an important difference to resources mobilized in the current secessionist movements.